بررسی خصوصیات فیزیکوشیمیایی و متغیرهای فارماکوگنوزی مان انذروت براساس دستورالعمل سازمان بهداشت جهانی. - هادی اسماعیلی; علی داوودی; مسعود آزادبخت; محمد آزادبخت (Medical Journal of Tabriz University of Medical Sciences & Health Services)
Background: Anzaroot is a manna produced from Astragalus sarcocola Dymock (Family Leguminosae) that is widely distributed in Fars, Kerman, Baluchestan and Hormozgan in Iran. Since the study of the physicochemical properties and quality control (QC) of herbal materials results in the validation and standardization for clinical uses, in accordance with World Health Organization (WHO) guidelines, it is necessary to carry out for Anzaroot which has indication in traditional medicine. Methods: Anzaroot was identified and determinated scientific name by a systematic specialist after purchasing from Niak pharmaceutical co. in gorgan. Physicochemical and pharmacognostical properties of Anzaroot have been determinated According to the WHO guidlines. Results: Anzaroot is a very bitter, crisp and fragile manna and non-stick in dry state, which is seen as separate binary grains under the microscope. The moisture content, foreign matter, sucrose content, total ash and watersoluble ash were reported 5.25 ± 0.2, 2.8 ± 0.2, 12.09 ± 0.04, 9.8 ± 0.5 and 2.9±0.15, respectively. It has significant foaming index, 72% Solublity in water and less than 50% in 96% ethanol and not swelling index. The levels of lead, mercury and cadmium were 0.0006, 0.0002 and 0.0007 ppm and total flavonoid content was reported 18.61 μg/ml with respect to standard Quercetin at 415 nm. Conclusion: This study can be a novel idea for the discovery or development of pharmaceutical products based on Anzaroot of Iran and its diverse therapeutic properties, such as the common cold, contusion, and bone fracture in traditional medicine.